ECONOMIC AND ORGANIZATIONAL MECHANISMS FOR THE INNOVATIVE DEVELOPMENT OF HOSPITALITY SERVICES - Amonov, Shakhrukh (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article analyzes economic and organizational mechanisms that facilitate innovative development in hospitality services. The research identifies key tools and management practices that enhance innovation implementation and service quality. The findings emphasize the importance of integrated mechanisms for improving competitiveness in the hospitality sector. The study further examines the role of digital transformation, investment policies, and human resource development in fostering innovation within hospitality enterprises. Particular attention is given to the adoption of modern technologies, including online booking systems, customer relationship management tools, and data-driven decision-making processes. In addition, the article highlights the importance of organizational flexibility, strategic planning, and effective coordination between stakeholders in ensuring sustainable innovation. It is noted that collaboration between public institutions and private businesses plays a significant role in creating a supportive environment for the development of hospitality services. The paper concludes that the implementation of well-structured economic and organizational mechanisms significantly contributes to the modernization of hospitality services, enhances customer satisfaction, and strengthens the competitive position of enterprises in both domestic and international markets.